Scientific information management in the research education of Medicine students - Elso Manuel Cruz Cruz; Eslhey Sánchez Domínguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
In any scientific research it is very important to achieve an appropriate information management to allow creating and transmitting new knowledge. In the context of the academic scientific activity, we approach the importance of including in the academic syllabus the training in scientific information searching in the Web. The reference to an experience in the medical school "Dr. Zoilo Marinello Vidaurreta" supports the idea of increasing the abilities and knowledge of students in scientific information searching from the academic years to enhance their research skills.